Measuring the Quality of Higher Education Website using Webqual Method and Importance-Performance Analysis - Effendi Muftikhali, Qilbaaini; Satria, Deki; Nurul Jamilah, Eva (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Website is one of the necessities needed by organizations, including educational organizations. Telkom University Jakarta Campus (TUJC) is an educational organization that needs it. Analysis methods needed to be conducted to find what needed to be improved. WebQual is utilized to gain this insight. Web Quality Index and Importance Performance analysis are performed to calculate the results. The results of the Web Quality index show that users' perspective is 60% on average and got a negative gap analysis. Therefore, the website needs improvements to satisfy the user. Importance Performance Analysis is used to find the indicator that needs improvement. The Importance Performance Analysis shows that timely website information and security are the main priority for improvement.